Ma vie en rose : olhares sobre infância, educação e gênero - Melo, Pedro Aparecido Barreto de (2018)
The cinematographic productions are considered as media texts that permit the construction of meanings that are related to how society conceives childhood. This research aims to comprehend teachers’ conceptions from childhood, gender and sexuality discourses present in the film “Ma vie en rose”, of Alain Berliner, which treats about the conflicts of a child in school, family and the neighborhood, provoked by his experiences with his own body that escape from a normative masculinity. The specific aims of this research are: how does the film bring to the childhood universe gender and sexuality questions? Which tensions are present between the teachers’ childhood conceptions and the childhood representations portrayed by the film? Which meanings about the relation between childhood, gender and sexuality do the teachers construct through the film? The theoretical and methodological contributions are: the enunciation theory of Mikhail Bakhtin in order to analyze the teachers’ discourses in dialogue with the film’s discourses; the children studies; and the gender studies. The research has consisted in discussion groups about the film “Ma vie en rose” conducted with pre-school and elementary school teachers that became from the public educational network, in Rondonópolis, Mato Grosso. Besides this, these teachers participated in the Education Observatory Program (Obeduc)/CAPES, linked to the Post-graduation Program in Education (PPGEdu). We observed, in the teachers’ discourses analysis, that the most recurrent meanings on the childhood, gender and sexuality theme were: the estrangement of children bodies that escape from a binary gender identity; the need to oversee, preview and categorize these bodies through the science validation; and the sexuality association with dangers, risks and pathologies.